1981
DOI: 10.1037/0096-1523.7.6.1303
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus repetition effects on attention to words and colors.

Abstract: Mere observation of 30 presentations of a colored form results in slower reaction time responses to the familiarized stimulus than to a comparable novel stimulus. Prior research suggest that this result is due to two subsidiary effects of repetition: alertness decrement and encoding facilitation. Four experiments were conducted to compare the effects of stimulus repetition on colors and words. The two-factor theory of repetition was found to hold for words as well as for colors; for words, in contrast to color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…However, in accord with their two-factor theory, this effect was reversed when the interval between the prefamiliarization and test trials was increased from 0 to 30 min, allowing the inhibitory factor to dissipate and the opposing facilitatory factor to dominate. In a follow-up study, Kraut, Smothergill, and Farkas (1981) observed comparable effects with word stimuli. Pre familiarization retarded reaction time to words under conditions designed to more heavily weight the inhibitory factor but enhanced reaction time under conditions designed to more heavily weight the facilitatory factor.…”
Section: Perceptual Inhibition Of Expected Inputsmentioning
confidence: 71%
“…However, in accord with their two-factor theory, this effect was reversed when the interval between the prefamiliarization and test trials was increased from 0 to 30 min, allowing the inhibitory factor to dissipate and the opposing facilitatory factor to dominate. In a follow-up study, Kraut, Smothergill, and Farkas (1981) observed comparable effects with word stimuli. Pre familiarization retarded reaction time to words under conditions designed to more heavily weight the inhibitory factor but enhanced reaction time under conditions designed to more heavily weight the facilitatory factor.…”
Section: Perceptual Inhibition Of Expected Inputsmentioning
confidence: 71%
“…One last possibility to consider is that in younger adults, repeated exposure to the same irrelevant stimulus (such as a word or a color) typically results in slower responses to the familiarized stimulus than to a comparable novel stimulus because of a habituation of brain responses to those stimuli (Fabiani, Low, Wee, Sable, & Gratton, 2006) and decreased alertness (Cecil, Kraut, & Smothergill, 1984;Kraut, Smothergill, & Farkas, 1981). However, the fact that responses to familiarized go (previous nogo) stimuli became faster from the first to the second block of the second task in the younger group rules out an alertness decrease account for repeated stimuli to explain the current pattern of results.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the case of the word stimulus, the facilitation of its encoding was brought about more strongly than the reduction of its alertness, the result of which was a decrease in RT. On the contrary, in the case of the color stimulus, the reduction of its alertness was more larger than the facilitation of its encoding, and in which case the RT increased (Kraut et al, 1981). Accordingly, it can be argued that the above mentioned " stimulus repetition effect " occurs even in the case of irrelevant stimulus in this experiment.…”
Section: Discussionmentioning
confidence: 46%
“…How can this result be explained ? Kraut, Smothergill, and Farkass (1981) reported that the stimulus presented repeatedly changed their alertness " and encodability" which were known as two of the three factors of attention (Posner & Bois, 1971), and that responses to these stimuli were influenced by these factors. In general, they claimed that repetitive presentation of a stimulus reduced its alertness (to increase the RT) and facilitated its encoding (to decrease the RT), and the relative strength of these changes might increase or decrease the RT to the stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation